Cooperative Strategy in Increasing the Competitiveness of MSMEs in the Digital Transformation Era - Yunesia Pramesthi; Eni Susilowati (Journal of Economics and Social Sciences (JESS), 2026)
The development of digital technology has brought major changes to economic activities, especially in the micro, small, and medium enterprises sector which plays an important role in economic growth. Changes in market behavior and increased use of technology encourage the need for cooperative-based economic institutional strengthening strategies to increase the competitiveness of MSMEs. This research aims to analyze cooperative strategies in increasing the competitiveness of MSMEs in the era of digital transformation. The method used is a literature review by analyzing 20 scientific articles in 2022–2026 related to cooperatives, MSMEs, and economic digitalization. The results of the study show that operational digitalization, the use of e-commerce, the strengthening of information systems, and the increase in the capacity of human resources have a significant impact on increasing the competitiveness of MSMEs. Cooperatives play a role in providing access to financing, business assistance, and the integration of MSMEs into the digital ecosystem. The findings also show that collaboration between cooperatives and digital technology is able to expand the market and increase business efficiency.